Introduction to finance - Melicher, Ronald W (John Wiley, 2011)
Business managers will gain a basic understanding of the complex world of finance with this engaging book. It presents a balanced survey of the three main areas of finance: institutions and markets, investments, and financial management. The examples have been completely updated throughout to provide the most relevant information. Discussions of small business practice help them gain a better understanding of small Finance,Finance Norton, Edgar 25550 26421 eng 9780132455916 428.24 S365 Schoenberg, Irene E an integrated skills approach Irene E Schoenberg, Jay Maurer xxiii, 314 p. Focus on grammar 1 ill. 27 cm Schoenberg, Irene E,Maurer, Jay New York, N.Y. Pearson Education 2012 English language English language Maurer, Jay 25551 26214 eng 9780521602204 428.24 R514 Richards, Jack C. Jack C. Richards with Jonathan Hull and Susan Proctor 1 v. Interchange ill. 28 cm Richards, Jack C.,Hull, Jonathan,Proctor, Susan Cambridge,New York Cambridge University Press 2005 English language w1w Communication, International English language,Communication, International Hull, Jonathan,Proctor, Susan 25552 26272 eng 9780130238689 w1w 0785466630 372.4 S642/A Smith, Nila Banton Nila Banton Smith 176 p. Be a better reader ill. 28 cm Smith, Nila Banton Upper Saddle River, NJ Pearson 2009 Content area reading w1w Content area reading w1w Reading comprehension Content area reading,Content area reading,Reading comprehension 25553 26589 Vie 658.3 Nh121 Lê, Hữu Quốc Nhân Luận văn thạc sĩ Quản lý kinh tế. Ngành: Quản lý kinh tế. Mã ngành: 60340410 Lê Hữu Quốc Nhân ; Huỳnh Văn Hồng (hướng dẫn khoa học) viii, 73, 10 tr. Phát triển nguồn nhân lực ngành giao thông vận tải tỉnh Bến Tre (giai đoạn 2017 - 2022) ill. 30 cm Lê, Hữu Quốc Nhân,Huỳnh, Văn Hồng,Ủy ban Nhân dân tỉnh Trà Vinh Trà Vinh Trường Đại học Trà Vinh 2018 Quản trị nhân sự w1w Quản lý nhân sự w1w Personnel management Quản trị nhân sự,Quản lý nhân sự,Personnel management Huỳnh, Văn Hồng người hướng dẫn khoa học Ủy ban Nhân dân tỉnh Trà Vinh Trường Đại học Trà Vinh 25554 26299 eng 9780136133285 428.24 B712 Bonesteel, Lynn grammar to communicate Lynn Bonesteel, Samuela Eckstut-Didier xv, 256 p. Center Stage 2 ill. 28 cm Bonesteel, Lynn,Eckstut-Didier, Samuela White Plains, N.Y. Pearson Longman 2008 English language w1w English language English language,English language Eckstut-Didier, Samuela 25555 26313 eng 0538722975 w1w 9780538722971 302.2242 T584 Timm, Paul R. Speech Communication Paul R. Timm viii, 184 p. The ill. 28 cm Timm, Paul R. Cincinnati, Ohio South-Western 2000 Oral communication The Basics of Speech Communication targets effective oral communication skills used in day-to-day living. Short, concise content delivers a thorough approach with clear-cut examples and exercises to reinforce learning. Use of current technology including the Internet have been incorporated throughout as well as the SCANS workplace readiness skills. Humor is also added to emphasize key principles and concepts Oral communication 25556 26549 Vie 658.8384 Th300 Võ, Xuân Thi Luận văn thạc sĩ Quản trị kinh doanh. Ngành: Quản trị kinh doanh. Mã Ngành: 60340102 Võ Xuân Thi ; Phạm Văn Tài (hướng dẫn khoa học) viii, 74, 18 tr. Xây dựng chiến lược kinh doanh dịch vụ bảo hiểm phi nhân thọ tại công ty bảo hiểm Bảo Long Cần Thơ giai đoạn 2017-20025 minh họa 27 cm Võ, Xuân Thi,Phạm, Văn Tài,Ủy ban Nhân dân tỉnh Trà Vinh Trà Vinh Trường Đại học Trà Vinh 2018 Strategic planning w1w Kế hoạch chiến lược w1w Quản trị chiến lược Thư mục: tr.74 Quản trị chiến lược,Strategic planning,Kế hoạch chiến lược Phạm, Văn Tài người hướng dẫn khoa học Ủy ban Nhân dân tỉnh Trà Vinh Trường Đại học Trà Vinh 25557 26220 Vie 352.4 Đ552 Phạm, Văn Đức Luận văn thạc sĩ Quản lý kinh tế. Ngành: Quản lý kinh tế. Mã ngành: 60340410 Phạm Văn Đức ; Nguyễn Hữu Đặng (hướng dẫn khoa học) xi, 113 tr. Nâng cao hiệu quả quản lý tài sản tại Trường Đại học Trà Vinh 28 cm Phạm, Văn Đức,Nguyễn, Hữu Đặng,Ủy ban Nhân dân tỉnh Trà Vinh Trà Vinh Trường Đại học Trà Vinh 2017 Finance,public Finance,public Nguyễn, Hữu Đặng người hướng dẫn khoa học Ủy ban Nhân dân tỉnh Trà Vinh Trường Đại học Trà Vinh 25558 26228 eng 9780071288576 425 B875 Brouka, Milada Milada Broukal xvi, 182 p. Grammar form and function ill. 28 cm Brouka, Milada New York, NY McGraw-Hill ESL/ELT 2005 English language w1w English language Provides a visual context within the grammar charts for learning and retaining vocabulary and grammar. This title integrates study of new structures (form) with information on how to use them and what they mean (function). Its comprehensive grammar coverage ensures thorough and effective presentation of different basic structures English language,English language 25559 26498 eng 9780131986749 428.34 C331 Carver, Tina Kasloff English in everyday life Tina Kasloff Carver, Sandra Douglas Fotinos-Riggs, Carolyn Graham 185 p. A conversation book 1 ill. 28 cm Carver, Tina Kasloff,Fotinos-Riggs, Sandra Douglas,Graham, Carolyn [New York] Pearson Longman 2006 English language w1w English language English language,English language Fotinos-Riggs, Sandra Douglas,Graham, Carolyn 25560 26499 eng 9781413009309 428.0076 P338 Pavlik, Cheryl Cheryl Pavlik xii, 204 p. Hot topics 3 ill. 27 cm Pavlik, Cheryl Boston, MA Thomson/Heinle 2006 English language w1w Reading comprehension English language,Reading comprehension 25561 26212 eng 97808521602228 428.24 R514 Richards, Jack C. Jack C. Richards with Jonathan Hull and Susan Proctor 1 v. Interchange ill. 28 cm Richards, Jack C.,Hull, Jonathan,Proctor, Susan Cambridge,New York Cambridge University Press 2005 English language w1w Communication, International English language,Communication, International Hull, Jonathan,Proctor, Susan 25562 26435 eng 9789574832828 808.6 L651 53 p. Letter town ill. 27 cm Taipei Tung Hua Book Co 2004 English language English language 25563 26443 eng 0230020453 w1w 9780230020450 428.24 G381/B1 Gershon, Steven Student Book Steven Gershon, Chris Mares 118 p. New English Upgrade 1 ill. 28 cm Gershon, Steven,Mares, Chris Oxford Macmillan Education 2007 English language English language Mares, Chris 25564 26207 eng 9780131840089 428.24 R839 student book Michael Rost ... [et al.] vii, 145 p. WorldView 3 ill. 28 cm White Plains, N.Y. Longman 2005 English language Unit 1 Nice to see you again.Unit 2 Why women ironUnit 3 Living in luxuryUnit 4 Allergic reactions Review 1World of Music 1 Unit 5 A typical dayUnit 6 It's absolutely true!Unit 7 Eating outUnit 8 It's deal! Review 2 Unit 9 The riverUnit 10 On the other handUnit 11 Trading spacesUnit 12 A soccer fan's website Review 3World of Music 2 Unit 13 Green cardUnit 14 What's that noise?Unit 15 Mumbai SoapUnit 16 The message behind the ad Review 4 Unit 17 WillpowerUnit 18 Wave of the futureUnit 19 Made in the U.S.A.Unit 20 At the movies Review 5World of Music 3 Unit 21 How polite are you English language Rost, Michael 25565 26235 eng 9780071114295 818.5209 S237/W2 Santos, Manuel dos Manuel dos Santos iii, 76 p. My world ill. 28 cm Santos, Manuel dos New York McGraw-Hill ESL/ELT 2006 English language Integrates the day-to-day aspects of teenagers' lives with real-life English learning situations and models. This title covers the four skills of reading, writing, listening, and speaking in a meaningful way. It includes theme-based units that appeal to teenagers which combine language input with skills work English language 25566 26429 eng 9789574831302 805.18 L693 Lian, Tammy Tammy Lian, Dai Chih - Wei 171 p. My life in Canada ill. 24 cm Lian, Tammy,Chih - Wei, Dai Taipei Tung Hua 2011 English language English language Chih - Wei, Dai 25567 26430 eng 9780132463027 w1w 0132463024 428.24071 B985 Butler, Linda a reading and vocabulary text Linda Butler 241 p. New password 3 ill.